PENERAPAN MODEL PENYEMBUHAN DENGAN REGRESI COX HAZARD PROPORSIONAL PADA PENYAKIT KANKER KOLOREKTAL - Wirna Arifitriana; Danardono Danardono (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2019)
Survival analysis is a statistical technique used to analyze the data, aims to determine the variables that affect the outcome of a beginning to end the incident. One model of survival is a cure model is useful for estimating the proportion of patients who recover and the probability of survival of patients who did not recover until the deadline given. Analysis on Cox regression cure model Hazard Proportional with Maximum Likelihood Estimates and Algorithm Expectation Maximization (EM). Keywords: Cox Proportional Hazard Cure Model, MLE, EM algorithm, likelihood ratio test, Wald test.